(untitled) (Conferencea, 2022)
The article describes the ichthyological study of Dengizkul Lake which is the largest one in Bukhara region as well as its water supply, hydrochemical composition of water, ichthyofauna and its development, its condition in different years, the importance of fishery, bioecological characteristics of fish species that are fished or not fished.